Diseño de un sistema de limpieza mediante ciclos térmicos en línea al turbo-expansor de la U-002 de la Refinería de Cartagena para incrementar su disponibilidad operativa - Iriarte LLamas, Rafael Antonio; Revollo Carreazo, Alexander De Jesus (Universidad Antonio Nariño, 2023)
The catalytic cracking reaction is endothermic in nature and produces coke as a by-product deposited on the circulating catalyst. The process uses the heat of combustion of the coke as an energy source, for which a large amount of air is required. For the regenerator of the unit, the combustion product gas has a large amount of energy that is used through the energy recovery system installed in the unit, which consists of the following components: starter motor, motor/generator, axial compressor and turbo-expander. The size of the motor/generator allows it to provide up to 70% of the power required for the unit's design case, and the power recovered by the Turbo-Expander is essential to reach 100% of the unit's capacity and save consumption of energy. A fundamental aspect of the operation is the catalyst, which is a fluidized solid in air or steam that circulates between the reactor and the regenerator. On the regenerator side, a solids separation (cyclone) technology is provided to minimize the discharge of particulate matter to the turboexpander, where the turboexpander removes the available energy from the gas in an attempt to maximize runtime, which is seen affected by progressive deposition.